Aleksandra Novakov: The Pillars of Serbian Education: Serbian Secondary Schools in the Ottoman Empire 1878-1912 - Šešum, Uroš S. (Sociološki pregled, 2018)
This paper presents a review of the monograph The Pillars of Serbian Education, Serbian Secondary Schools in the Ottoman Empire 1878-1912 by Dr. Aleksandra Novakov. Prior to presenting the structure and signifcance of the work, there is a brief outline of the general historical context in which Serbian educational and political activity had operated in the Ottoman Empire in the decades preceding the First Balkan War. The scope and the signifcance of the monograph for Serbian science were highlighted. Keywords: Ottoman Empire, historiography, Aleksandra Novakov, education, Old Serbia.